The Dynamics of Food Demand in Algeria: A Differential System Approach - Benmehaia, Mohamed Amine; Dhehibi, Boubaker (Classiques Garnier, 2024)
In Algeria, it happens that the quantitative assessment of food consumption patterns is less present in analytical studies of demand. The food consumption pattern has undergone since independence (1962) radical and even drastic changes, and this is due to a multitude of factors of various origins. The most important aspect is the confrontation of traditional patterns (before nineteenth century) with the advent of the modernity (since the colonization era). According to Chikhi & Padilla (2014), modernity is gaining ground and acquiring greater shares over tradition in an increasingly globalized national market.